Textbooks and the women’s participation in armed struggle in Brazil (Tempo e Argumento, 2021)
This article analyzes a set of History textbooks from the catalogs of the National High School Textbook Program (PNLEM) of 2008 and 2018, with the aim to analyze the ways in which women’s participation in the armed organizations in Brazil, between 1968 and 1974, is presented. The reason for focusing on the theme is justified by the place that the armed struggle has in the history and memory of the Brazilian dictatorship, by the presence of the theme in the selected school textbooks and, also, by the existence of research and publications on the women’s participation in these events. The text is organized in three parts: in the first, we present the PNLEM, the textbooks to be examined and the reviews made about them in the 2008 and 2018 Catalogs, as part of the evaluation process provided for the Program; in the second part, we explore the contents of the selected books; in the third and last part, we dialogue with the historiography about women in armed struggle and about the history textbook.Keywords: history textbooks; women; Brazilian dictatorship; armed struggle.